Role of SGLT2 inhibitors in the treatment of visceral obesity - M. A. Druzhilov; T. Yu. Kuznetsova (Кардиоваскулярная терапия и профилактика)
The increasing prevalence of obesity limits the prevention of the development and progression of chronic non-communicable diseases. The central methods of risk correction associated with obesity are lifestyle changes and prescribing medications for obesity. Sodium-glucose co-transporter type-2 (SGLT2) inhibitors, also called gliflozins, which are used for type 2 diabetes, have shown additional positive effects on surrogate and hard endpoints in numerous studies. This became the basis for a detailed study of their cardio- and neuroprotective effects and for conducting studies with such drugs in other cohorts of patients. This review presents the results of studies that examined the effect of SGLT2 inhibitors on body weight in overweight and obese individuals, the quantitative characteristics and functional activity of visceral adipose tissue, as well as other components of visceral obesity, and discusses the potential of using these drugs in the management of such patients.